Quality management of mathematics learning in realizing professional teachers in madrasah - Hidayah, Nurul; Mustofa, Nuryadin Ali; Harjati, Purwiro; Pahrudin, Agus (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: The quality of education is a crucial indicator of a teacher's professionalism, especially in complex subjects like mathematics. Improving the quality of mathematics education requires structured initiatives aimed at developing teacher professionalism through effective changes.Aim: This study aims to analyze and identify quality management practices in mathematics education and how these practices contribute to the development of teacher professionalism in madrasah.Method: This research employs a qualitative descriptive approach. The objects of the study include quality management in education, mathematics learning, and professional teachers, while the subjects are mathematics teachers teaching in madrasas. Data were collected through observation and interviews. Data analysis was conducted which involves data reduction, data presentation, data display, and conclusion.Results: The research findings indicate that during the planning stage, teachers design lessons by considering the existing curriculum, lesson plans (RPP), and innovative teaching methods and media, adapting to technological and communication advancements. Teachers are selected based on their educational qualifications and mathematical skills. Organization involves preparing teachers to manage learning activities, including providing assistance to students in need. Leadership training and development are also provided to enhance classroom management. The implementation of learning consists of introductory, core, and closing stages, focusing on developing teachers' creativity and work ethic. Evaluation is conducted after the learning process to identify and address deficiencies in mathematics teaching and assessment.Conclusion: The quality of mathematics education in fostering professional teachers in madrasas is based on management functions, namely planning, organizing, implementing, and evaluating.